(untitled) (Bangladesh Agronomy Journal, 2021)
A field experiment was conducted during the period from January to May 2014 to study the response of growth, flower dropping, pod setting and yield of two soybean varieties to foliar fertilization of urea at early stage of flowering. Soybean varieties, BARI Soybean-5 and BARI Soybean-6, were feeded with four supplemental foliar spray treatments of fertilizer, viz. M1: Control i.e., no additional nutrient spray; M2: 20% of recommended urea spray at flowering; M3: 20% dose of the recommended MoP; and M4: 20% dose of the recommended DAP at early flowering stage. The experiment was laid out in a split-plot design with three replications. There was no significant effect of variety, fertilization spray or their interaction observed on growth parameters. However, flower and pod dropping was affected with higher flower dropping (55.2%) in BARI Soybean-5 and maximum pod dropping (16.44%) with DAP spray treatment. Higher yield attributes’ values such as seeds pod-1 (2.42), seed yield (1.18 t ha-1), stover yield (1.02 t ha-1), and biological yield (2.21 t ha-1) were obtained with foliar DAP spray treatment. The interaction of BARI Soybean-5 and foliar DAP spray showed the highest seed yield (1.48 t ha-1), stover yield (1.26 t ha-1) and biological yield (2.75 t ha-1). Bangladesh Agron. J. 2020, 23(2): 111-117